Modelo De Control De Los Procesos Constructivos De Viviendas De Hasta Dos Plantas - Corella Prieto, Leticia de los Ángeles (2017)
Every project has a PROJECT LIFE CYCLE that is a series of phases through which a project (HOME-PLANNING-EXECUTION-FOLLOW-UP AND CONTROL-CLOSURE) goes through, not being construction projects the exception. In all sectors of the Construction and housing is very common that the works are not delivered within the contracted term or with the initial budget, and in some cases does not satisfy the quality of the same to their owners. Aiming at this thesis to establish a "MODEL OF CONTROL OF THE CONSTRUCTIVE PROCESSES OF HOUSES OF UP TO TWO PLANTS". Where they determine the necessary fundamentals that affect to carry out a CONTROL MODEL. In this thesis we have analyzed several guidelines, however for we have been based on the PMBOK guide that is a rule to direct the majority of projects. For Monitoring and Control we have tools that are: INTEGRATION MANAGEMENT: Monitoring and controlling the work Integrated change control, REACH MANAGEMENT Scope validity Control Scope TIME MANAGEMENT Control the Performance of the Schedule, COST MANAGEMENT Control the Costs, QUALITY MANAGEMENT Control the Quality of the Components of each Activity, Control the quality of the activities based on the technical specification, COMMUNICATIONS MANAGEMENT Integrated control of the communications, MANAGEMENT OF THE ACQUISITIONS Control of the acquisitions and MANAGEMENT OF THE INTEREST Control Stakeholder participation, based on the PMI standards.